2006
DOI: 10.3390/s6080962
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Aqueous Solutions of a Cationic Calix[4]arene: A Comparative Study of Dye–Calixarene and Dye–Surfactant Interactions

Abstract: Among different types of calixarenes, the water–soluble ones are of especial interestbecause of their possible applications in biochemical research. In order to elucidate the natureof aqueous solutions of a cationic amphiphilic calixarene, substituted tetrapropoxycalix[4]arene bearing hydrophilic choline groups at the upper rim, we studied vis–spectroscopically the influence of the above system on the acid–base behavior of threeindicator dyes, namely, 2,4-dinitrophenol, bromophenol blue, and N,N/-dioctadecylrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 29 publications
(35 reference statements)
2
23
0
Order By: Relevance
“…The first example from this family, CX3, has already been synthesized and characterized before. [31] However, its studies showed that it forms micellar structures only at rather high concentrations (CMC near 2.5 mm) in water. [30] To improve the self-assembling ability of this molecule, we extended the length of the alkyl chains from propyl to octyl.…”
Section: Resultsmentioning
confidence: 99%
“…The first example from this family, CX3, has already been synthesized and characterized before. [31] However, its studies showed that it forms micellar structures only at rather high concentrations (CMC near 2.5 mm) in water. [30] To improve the self-assembling ability of this molecule, we extended the length of the alkyl chains from propyl to octyl.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, Furel et al. [ 35 , 36 ] have been studied the experimental infrared spectrum of the free CX[4] molecule. The experimental spectrum shows O–H stretching vibration in the region varying from 2900 to 3500 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account self-aggregation of the studied aminocalix (Arimori et al, 1995), it is likely that drug solubilization by aminocalix is based on micellar effects. The interaction between CAs with a similar ionic struc- ture and dyes (Mchedlov-Petrossyan et al, 2006 has been studies and it has been proposed that the possible mechanism of interactions is due to the micellar effect rather than docking of the indicator dyes into calixarene cavities. Thus, relation of aminocalix's solubilizing ability to drug interaction with lipophilic vesicle regions should not be excluded.…”
Section: Tablementioning
confidence: 99%